Transformasi Laplace



Carilah Nilai $f(t)$ dari $\mathcal{L}\left(\dfrac{6}{s^2-4s-5}\right)$ 


Jawab: 


\begin{eqnarray*}
\frac{6}{s^2-4s-5}&=&\frac{6}{(s-2)^2-9}\\
&=&\frac{3}{(s-2)^2-9}+\frac{3}{(s-2)^2-9}\\
\end{eqnarray*}

Karena $\mathcal{L} \sinh(at)=\dfrac{a}{s^2-a^2}$ dan $\mathcal{L} e^{2t}=\dfrac{1}{s-2}$ Maka :
 \begin{eqnarray*}
\mathcal{L}\left(\dfrac{6}{s^2-4s-5}\right)&=&\mathcal{L}\left(\frac{3}{(s-2)^2-9}+\frac{3}{(s-2)^2-9}\right)\\
&=&e^{2t}\sinh(3t)+e^{2t}\sinh(3t)\\
\mathcal{L}\left(\dfrac{6}{s^2-4s-5}\right)&=&2e^{2t}\sinh (3t)
\end{eqnarray*}

Selesai...